Conducting Unsupervised Virtual Reality User Studies Online - Mottelson, Aske; Petersen, Gustav Bøg; Lilija, Klemen; Makransky, Guido (Frontiers in Virtual Reality, 2021)
Conducting user studies online and unsupervised instead of in laboratories gives quick access to a large and inexpensive participant pool. It is however unclear if data sourced this way is valid, and what the best practices for conducting unsupervised VR studies are. The restrictions on laboratory access experienced during COVID-19 further necessitate the development of valid procedures for remote data collection, especially for research fields such as VR that heavily rely on laboratory studies. In this paper we validate the method, by reporting our experience with conducting two online VR studies amidst the pandemic. With these, we investigate whether it is feasible to collect valid data across in-VR survey responses and hand tracking. We report a good reliability of collected data, which requires only slightly more sanitation than a comparable laboratory study. We synthesize our experiences into practical recommendations for conducting unsupervised VR user studies using online recruitment, which can greatly reduce barriers to conducting empirical VR research and improve the quantity of VR user studies, regardless of laboratory availability.